Self-Interest in Canadian Foreign Policy: The Principle and Practice of Internationalism - MacLean, George (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2008)
Internationalist impulses in Canadian foreign policy are best understood from both functional and ideological perspectives. This article suggests that the practice and principle of Canadian internationalism reflect a set of core values emanating from domestic society, as well as an indispensable emphasis on multilateralism in foreign policy. The article explores the tradition of Canadian internationalism, multilateral instincts evident in collective action, and the core values which are entwined in the constitutional premise of "peace, order, and good government" (POGG). The article concludes that, though paradoxical upon first examination, Canada's cooperative internationalist tradition was and remains fundamentally self-interested.